Resilience to adversity is associated with increased activity and connectivity in the VTA and hippocampus - Richter, Anja; Krämer, Bernd; Diekhof, Esther K.; Gruber, Oliver (NeuroImage: Clinical, 2019)
Accumulating evidence suggests altered function of the mesolimbic reward system resulting from exposure to early adversity. The present study investigated the combined long-term impact of adversity until young adulthood on neuronal reward processing and its interaction with individual resilience processes. In this functional magnetic resonance imaging study, 97 healthy young adults performed a reward-based decision-making task. Adversity as well as resilience were assessed retrospectively using the validated childhood trauma questionnaire, trauma history questionnaire and a resilience scale. Subjects with high adversity load showed reduced reward-related bottom-up activation in the ventral striatum (VS), ventral tegmental area (VTA) and hippocampus (HP) as compared to the low adversity group. However, high resilience traits in individuals with high adversity load were associated with an increased activation in the VTA and HP, indicating a possible resilience-related protective mechanism. Moreover, when comparing groups with high to low adversity, psychophysiological interaction analyses highlighted an increased negative functional coupling between VS and VTA as well as between VS and anteroventral prefrontal cortex (avPFC) during reward acceptance, and an impaired top-down control of the VS by the avPFC during reward rejection. In turn, combination of high adversity and high resilience traits was associated with an improved functional coupling between VTA, VS and HP. Thereby, the present findings identify neural mechanisms mediating interacting effects of adversity and resilience, which could be targeted by early intervention and prevention.